The Impact of Social Media on ESL Students’ Writing Skills: A Case Study of Uzbekistan State World Languages University - Tulanboyeva, Xandona Azamatjon qizi (The Lingua Spectrum, 2026)
In recent years, social media has become an integral part of students’ everyday lives, influencing learning behaviors and communication patterns. This study investigates the impact of digital platforms on the development of writing skills among ESL students at Uzbekistan State World Languages University. As well as, using a quantitative approach through a three-stage survey (preparatory, implementation, and analytical), the research analyzes the experiences of 26 third- and fourth-year students. The findings reveal that while Telegram is the dominant educational tool (65.4%), its pedagogical potential remains only moderately realized. The study confirms that students favor a blended model where digital interaction complements traditional instruction. Key challenges identified include the “infiltration” of informal patterns into academic writing and a prioritization of speed over accuracy. Moreover, the research concludes that purposeful integration of social media can significantly enhance motivation and vocabulary, provided that structured teacher scaffolding and clear assessment criteria are in place.